Identifying Needs and Opportunities for Local Government Environmental Education and Training in South Africa - Lausanne Olvitt; Tyson Hamaamba (Environmental Association of Southern Africa, 2006)
Effective environmental management and public engagement with environmental concerns are needed for the attainment of sustainable development goals and socio-ecological balance in local government contexts. This vision is clearly articulated in international environmental policy frameworks and in South Africa's national and regional legislation. However, policy and legislation fall short of identifying the range of a priori competences required by local government officials and environmental managers before well intended policy can be translated into effective practice. This paper reports on recent research into identifying the underlying competences required for better environmental management and the establishment of education and training processes for local government managers. The research draws on the notion of 'applied competence' put forward by South Africa's National Qualifications Framework, and argues that greater attention needs to be paid to competencebased capacity building processes within local government departments if environmental sustainability and development goals are to be met. The paper draws on the researchers' experiences of formulating a national level generic competence framework for environmental management, and conducting an education and training needs analysis for the Makana Municipality in the Eastern Cape province of South Africa. Early findings suggest that a broad range of competences all have a role in ensuring the capacity and effectiveness of local governments to better manage their local environment. The paper argues that these are significant for the development of environmental education and training programmes in local government contexts.